Inclusive Leisure Among People on the Autismspectrum: Some Experiences in Museums - Molina Villalba, Carmen (Eikón / Imago, 2019)
Leisureis a human right. Everyone, regardless his or her condition, has the right to enjoy satisfactory leisure activities and experiences. However, when we talk about disability we find out too often that these leisure programs and activities are organised according to standardised oriented models as a mereway of spending free time, without taking into consideration the diversity and user´s wishes. This article studies the needs of autistic people for their full inclusion in museums and shows with different case studies to favor their normalized presence in society and turn these cultural products into permanent offer for the museums themselves.